2016
DOI: 10.3390/ijms17040426
|View full text |Cite
|
Sign up to set email alerts
|

The Retentive Strength of Cemented Zirconium Oxide Crowns after Dentin Pretreatment with Desensitizing Paste Containing 8% Arginine and Calcium Carbonate

Abstract: The effect of dentin pretreatment with Desensitizing Paste containing 8% arginine and calcium carbonate on the retention of zirconium oxide (Y-TZP) crowns was tested. Forty molar teeth were mounted and prepared using a standardized protocol. Y-TZP crowns were produced using computer-aided design and computer-aided manufacturing (CAD-CAM) technology. The 40 prepared teeth were either pretreated with Desensitizing Paste or not pretreated. After two weeks, each group was subdivided into two groups, cemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 24 publications
1
15
2
2
Order By: Relevance
“…In RMGIC group, the type of failure most frequently found was adhesive no matter whether P&B NT was applied, which has also been reported by Pilo et al (2016) and Dursun and Attal (2011). Classifications should be refined to make the difference between different severity of fluorosis in the further study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In RMGIC group, the type of failure most frequently found was adhesive no matter whether P&B NT was applied, which has also been reported by Pilo et al (2016) and Dursun and Attal (2011). Classifications should be refined to make the difference between different severity of fluorosis in the further study.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding failure modes, in RXU group, mixed failure was predominant regardless of P&B NT pretreatment, which agreed with the results of those who used self‐adhesive resin cements (Boing, Gomes, Gomes, Reis, & Gomes, ; Kim, Cho, Roh, & Shin, ). Pilo et al () have reported predominant failure mode for RelyX U200 was adhesive cement‐crown and the classification was not identical with this study. In RMGIC group, the type of failure most frequently found was adhesive no matter whether P&B NT was applied, which has also been reported by Pilo et al () and Dursun and Attal ().…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…No significant difference in the bonding strength of composites to enamel or dentin pretreated with this desensitizing paste has been reported [22][23][24]. In addition, pretreating dentin surfaces with Pro-Relief Desensitizing Paste prior to cementation did not affect the retention of complete cast metal crowns luted with a glass ionomer cement (GIC) [25] or the retention of zirconium oxide crowns luted with a resin-modified GIC or a self-adhesive resin cement [26].…”
Section: Introductionmentioning
confidence: 99%